Rancang Bangun Sistem Informasi Akuntansi menggunakan Metode Incremental – Studi Kasus di Koperasi Karyawan Coca Cola SIER - Muhammad Harist Murdani; Nurwahyudhi Widhiyanta; Surya Priyambudi; Muhammad Asrori (SMATIKA JURNAL, 2022)
Rapid technology advancement requires some business actors to change their habits. Koperasi karyawan Coca Cola is a conventional employee cooperative that has not implemented specific systems to manage its financial data. Problems arise when there is a need to change the daily transactional data in the previous month or even the previous year. In this study, we designed and implemented an accounting information system to facilitate the processing of its financial data until balance reports. In addition, we also added a new menu, a balance list recalculation for the purpose of upholding data integrity which may change due to changes in daily transactional data in the previous month or previous year. The result shows that the accounting information systems that has been developed and implemented is very helpful by shortening the time required by financial staff in managing daily transactional data and generating monthly accounting reports.